Analysis of Factors that Influence Interest in Playing Football in Adolescents - Andrianto, Joan Rhoby (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research uses a descriptive qualitative approach to identify factors that influence interest in playing football among teenagers in Peterongan District, Jombang. Data was collected through in-depth interviews and participatory observation of 20 teenagers aged 13-18 selected using purposive sampling and analyzed using thematic analysis techniques. The research results revealed four main themes that influence interest in playing football in teenagers: family support, sports facilities, peer influence, and the role of the media. Family support, both moral and material, has been proven to increase adolescent motivation. Adequate and well-maintained sports facilities are also crucial in supporting interest in playing. A positive social environment from peers encourages a spirit of competition and togetherness. In addition, mass media, through match broadcasts and football content on social media, provides inspiration and information that strengthens teenagers' interest in football. These findings provide important implications for the development of strategies to increase youth participation in the sport of soccer.